2016
DOI: 10.1039/c5cy01591j
|View full text |Cite
|
Sign up to set email alerts
|

Cascade enzymatic cleavage of the β-O-4 linkage in a lignin model compound

Abstract: The β-O-4 aryl ether linkages represent about 50% of all ethers in various lignins. At least three enzymatic\ud steps are required to break them down: a NAD+-dependent C-α dehydrogenase (such as LigD and L), a\ud glutathione lyase that releases guaiacol (i.e., a β-etherase such as LigE and F), and a glutathione-dependent\ud lyase (i.e., LigG). In this work the LigD, L, E, F, and G fromSphingobium sp. SYK-6 were overexpressed in E.\ud coli and purified with high yields. After characterizing the stability and ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 22 publications
1
29
0
2
Order By: Relevance
“…2A , D , and E ). Thus, although it has been suggested that LigG can hydrolyze both β-epimers of GS-HPV ( 24 ), this result, along with those published previously ( 21 ), supports the hypothesis that LigG has a strong preference for β( R )-GS-HPV. This direct comparison of substrate conversion to products in assays that differ only in the addition of LigG or NaGST NU allows us to conclude that use of the latter enzyme has advantages owing to its greater ability to release HPV from both GS-HPV epimers under comparable conditions in vitro .…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…2A , D , and E ). Thus, although it has been suggested that LigG can hydrolyze both β-epimers of GS-HPV ( 24 ), this result, along with those published previously ( 21 ), supports the hypothesis that LigG has a strong preference for β( R )-GS-HPV. This direct comparison of substrate conversion to products in assays that differ only in the addition of LigG or NaGST NU allows us to conclude that use of the latter enzyme has advantages owing to its greater ability to release HPV from both GS-HPV epimers under comparable conditions in vitro .…”
Section: Discussionsupporting
confidence: 89%
“…From information available in the literature, it has remained unclear whether the GSH lyase from Sphingobium strain SYK-6, LigG, has a preference for β( R )-GS-HPV ( 18 , 21 ) or is capable of cleaving the thioether linkages in both β( R )-GS-HPV and β( S )-GS-HPV ( 24 ). As the presence of NaGST NU resulted in cleavage of both β( R )-GS-HPV and β( S )-GS-HPV in this coupled reaction system ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, LigG had little to no activity with (␤S)-GS-HPV, suggesting involvement of an alternative GST in the conversion of (␤S)-GS-HPV (15,18). Recently, further detailed biochemical characterization of the ␤-aryl ether catabolic enzymes of SYK-6 and their orthologs in other bacterial strains, and structural analyses of LigD, LigL, LigE, LigF, and LigG have been performed (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). In addition, Erythrobacter sp.…”
mentioning
confidence: 99%